Intrinsic Atrial Myopathy Precedes Left Ventricular Dysfunction and Predicts Atrial Fibrillation in Lamin A/C Cardiomyopathy. (22nd December 2022) - Tremblay-Gravel, Maxime; Ichimura, Kenzo; Picard, Kermshlise; Kawano, Yumeko; Dries, Annika M.; Haddad, Francois; Lakdawala, Neal K.; Wheeler, Matthew T.; Parikh, Victoria N.
Abstract : Background: In Lamin A/C ( LMNA ) cardiomyopathy, atrial fibrillation (AF) commonly occurs before dilated cardiomyopathy, and the ability to predict its incidence is limited. We hypothesized that left atrial (LA) echocardiographic phenotyping can identify atrial myopathy and harbingers of AF. Methods: Echocardiograms from patients with pathogenic or likely pathogenic variants in LMNA (n=77) with and without reduced left ventricular ejection fraction (LVEF, <50%) were compared to healthy individuals (n=70) and patients with Titin truncating variant cardiomyopathy (TTNtv ) (n=35) with similar LVEF, sex, and age distributions. Echocardiographic analysis, blinded to genotype, included strain and volumetric measures of left ventricular and atrial function. The primary outcome was incident AF. Results: At baseline, 43% of the patients with pathogenic or likely pathogenic LMNA variants had a history of AF, including 26% of those with LVEF ≥50%. Compared with healthy subjects, the patients with pathogenic or likely pathogenic LMNA variants and LVEF ≥50% had reduced LA contractile strain ( LMNA, 11.8±6.1% versus control, 15.0±4.2%; P =0.003). Compared to LVEF-matched ( TTNtv ) patients, the patients with pathogenic or likely pathogenic LMNA variants and LVEF <50% displayed no difference in LA size, but a worse LA contractile dysfunction (6.4±4.7% versus 12.6±9.6%; P =0.02). Over a median follow-up of 2.8 (1.2–5.7) years, LA contractile strain was the only significant predictor of AF in multivariable Cox regression (hazard ratio, 4.0 [95% CI, 1.04–15.2]). Conclusions: LMNA cardiomyopathy is associated with early intrinsic atrial myopathy reflected by high AF prevalence and reduced LA contractile strain, even in the absence of LV dysfunction and LA dilation. Whether LA strain can be used as a monitoring strategy to detect and mitigate AF complications requires validation.